Dolphins! - Bokoske, Sharon; Davidson, Margaret, 1936-; Courtney (New York : Random House, 1993)
Introduces dolphins and their physical characteristics, behavior, social structure, intelligence, and interaction with humans
Keywords: Dolphins -- Juvenile literature; Dolphins